Frequency of treatments with conventional and implant-supported prostheses in patients treated at the dental center of a private university in Lima, Peru, over a four-year period - Solano Angeldonis, Kimberly Janet (2024)
Objective: To determine the frequency of the types of conventional prosthesis and implant-supported prosthesis treatments of patients who attended the Centro Dental Docente of Universidad Peruana Cayetano Heredia (CDD-UPCH), Lima-Peru, between 2016 and 2019. Materials and methods: Cross-sectional study. The CDD system database was used, from which 56 347 electronic medical records were obtained. The sample size was 382 electronic medical records. The variables were the following: type of prosthetic treatment (conventional or implant-supported), sex, age, educational level and place of residence. A bivariate analysis was performed using STATA 16.0 software. Results: A total of 60.21 % (n = 230) of the prosthetic treatments were conventional, with the removable partial prosthesis being the most frequent with 53.47 % (n = 123) and the overdenture the least frequent with 5.21 % (n = 12). A total of 39.79 % (n = 152) of the prosthetic treatments were implant-supported, with unitary implant-supported prosthesis being the most frequent with 40.13 % (n = 61) and multiple implant-supported prosthesis the least frequent with 10.53 % (n = 16). Conclusions: The frequency of conventional prostheses was higher than that of implant-supported prostheses. The removable partial and unitary implant prostheses were the most requested treatments in their respective groups.